Union revitalisation in advanced economies. Assessing the contribution of union organising (Basingstoke, 2009)
"After a decade of "union organizing" in Britain, the time has come to make a thoroughgoing assessment of it. This book evaluates the efficacy of the union organizing in terms of union strategies, tactics, styles and resources, and assesses the impact of differing regulatory regimes on union organizing."